EMPOWERING DISABILITIES THROUGH SKILLS BATIK IN CENTER GRIYA HARAPAN SOCIAL SERVICES FOR THE DISABLED, SOCIAL SERVICES OF WEST JAVA PROVINCE - Ani Mulyani (Universitas Pasundan, 2025)
People with disabilities often face challenges in fulfilling their rights, including the right to work and a decent living. This study aims to describe the empowerment of people with disabilities through batik skills at the Social Service Center. Home Hope Disabled Service Social Province Java West. Method study Which The method used was a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and document studies. The results of the study indicate that batik training has a positive impact on increasing economic independence by providing opportunities for people with disabilities to produce products with marketable value, thereby increasing income and financial independence. Furthermore, the support provided in this empowerment helps build self-confidence and enables them to participate more actively in society. This empowerment also serves as an inclusive platform that supports the development of their potential. Empowerment is carried out with a comprehensive approach that involves improving skills, providing resources, opportunities, and knowledge, as well as strengthening individual capacity to overcome the social and economic inequalities they face. Through the provision of batik skills, people with disabilities are empowered to take control of their own lives, improve their economic well-being, and actively participate in society. In addition, they also receive various facilities such as additional training in computer training and digital marketing training , as well as support in the form of wages, food allowances, housing, and social guidance. With empowerment through batik skills, people with disabilities can more empowered in undergo life socialize. Empowerment This not only provide technical skills, but also create an environment that supports integration social And development self person with disabilities disability. Study This highlight the importance of ongoing support and inclusive empowerment programs to improve the welfare of people with disabilities.